Application of Phosphate Solubilizing Fungi Indegenous Paddy Soil Increased P Availability, Rice Growth and Production - Dermawan Hutagaol; Nurma Ani; Aisyah Lubis (Budapest International Research and Critics University, 2021)
Phosphate solubilizing fungi (PSF) from paddy soil can used as biofertilizer to increase P availability.Aimed this experime nt was to increase P availability, growth and paddy rice production. The randomly complete block design used that consist two factors, eg. Dosage of PSF (A) and anorganic P fertilizer (F). Factor dosage of PSF (A) with four levels: without PSF; 2 kg PSF/plot; 4 kg PSF/plot and 6 kg PSF/plot. Factor anorganic P fertilizer with three levels: without anorganic P fertilizer; 50% anorganic P fertilizer and 100% anorganic P fertilizer. Experiment result showed that application of PSF increased P availaibility, growth and plant production more high than without application of PSF. Application of anorganic P fertilizer increased P availability, growth and plant production more high than without application of anorganic P fertilizer. Interaction between application of PSF with anorganic P fertilizer (4 kg PSF/plot + 100% anorganic P fertilizer) increased P availibility, growth and plant production more high than without application of PSF and anorganic P fertilizer (control).